UJI KETAHANAN 21 VARIETAS JAGUNG TERHADAP PENYAKIT KARAT DAUN - , DANAR WICAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leaf Rust Disease on corn is a obstacle factor in corn cultivation. The use of resistant varieties is one of the disease management strategies. This study aimed to test the resistance of some commercial and pre-commercial corn varieties to leaf rust disease. Tests were conducted in a plastic house and in the field. The plastic house test used Complete Randomized Design (CRD) with 11 treatments and 3 replications. This tests used 7 varieties of pre-commercial and 2 check resistant and susceptible varieties. The test in the field used 7 pre-comercial varieties and 6 comercial varieties with 2 check resistance and susceptible varieties. The field test used Randomized Complete Block Design with 3 replications. In the plastic house test, the level of corn resistance to leaf rust disease could not be determined because most varieties was death at 12 th week. However BMD 38 could delay the development of leaf rust disease, longer than other varieties until 10 week after planting, as long as resistance check varieties. In the field test, there was no corn varieties that was resistance to leaf rust disease after 12 th week after planting. However, MON 05, MON 28, BMD 36, BMD 37, BISI 816, BISI 2, BISI 18 and BISI 22 could delay leaf rust desease development until 8 th week after planting. The higher stomata density in corn the higher leaf rust disease intensity was the lower corn resistance to leaf rust disease.